Necrotizing Cervical Fasciitis, Retrospective study of Cases and management - Tawfique, Saleh A. (Sulaimani Journal for Pure and Applied Sciences, 2012)
Total nine patients of Cervicofacial Necrotizing Fasciitis (CNF) were treated at ENT Department Al Ain Hospital between September 2007 and September 2009. The out come of their management studied retrospectively and presented. All patients were evaluated regarding clinical manifestations, etiology and site of infection and details of their management were discussed. Majorities of patients were diabetic male adults. All patients had odontogenic infection as the primary source of infection, except one who had parapharyngeal abscess.. The bacteriology showed streptococci on top of the list, but all of them had multibacterial infections. Gentamycin, metronidazol, benzyle Penicilline and clindamycin represent a combination thearapy covering all gram negative, gram positive and anaerobes for all cases. Histopathology showed extensive tissue necrosis with dermal vascular necrosis. Mortality was 1/9 (11.1%). One patient died from his illness and others recovered after proper surgical and medical management. Details of their presentation, site of infection, bacteriological causes and out come of the management are discussed and results compared with other articles. We emphasize early diagnosis and initiation of both aggressive surgical (repeated debridement) and medical treatment (combinations of antibiotics) and a multidisciplinary approach is essential to minimize mortality.
Keywords: CNF; Fascitis